The Influence of Wages, Work Discipline on Work Productivity Mediated by Job Satisfaction in the Ikat Weaving Industry CV Silvi Mn. Paradila - Muhammad Agung Setiawan; Mohammad Yaskun; Sustyorini, Emalia Nova; Rivatul Ridho (Formosa Journal of Applied Sciences, 2024)
This research aims to determine the effect of wages, work discipline on work productivity, mediated by job satisfaction in the CV ikat industry. Silvi Mn Paradila. This research method uses descriptive quantitative methods. The data used in this research is primary data and secondary data. The sample used was 88 respondents. The sampling technique used is simple random sampling. The data analysis technique uses Structural Equation Modeling - Partial Least Square (SEM-PLS). The results of this research show that wages have a positive and significant effect on work productivity, work discipline has a positive and significant effect on work productivity, job satisfaction has a positive and significant effect on work productivity, wages have a positive and significant effect on work productivity mediated by job satisfaction, and work discipline positive and significant effect on work productivity is mediated by job satisfaction.